Peningkatan Trend Screentime selama Pandemi Covid 19 dan Efeknya pada Perilaku Anak - Istiqomah, Nurul; Roida Simanjuntak, Susi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2021)
Background. One of the policies carried out by WHO and the Indonesian government in increasing and handling Covid-19 is physical activity savings. This policy requires all people to stay at home more. Along with this, children's activities outside the home are also the foundation. Goal. To see the increase in screen time in children aged 4-12 years during the COVID-19 Pandemic and its effects on children's behavior problems. Method. This research with cross sectional design was conducted by using questionnaires to parents who have children aged 4-12 years. Questionnaire was distributed using Google Forms for 4 weeks via social media such as WhatsApp, Instagram, and Facebook. Questionnaire used in this study was the Strength and Difficulty Questionnaire (SDQ) questionnaire. Result. During 4 weeks, 74 respondents were obtained. The duration of screen time has a significant relationship with the total behavior problems in children (p = 0.024). Conclusion. Increasing the screen time beyond the recommended duration can cause various behavioral problems in children such as emotional problems, behavior and hyperactivity.